Increasing Student Interest in Reading and Literacy in Cilondong Elementary School Through Village Reading Corners - Intansari, Intansari; Rismawati, Neng; Rizky, Hadist; Fazriah, Siti; Satria, Restu; Gus, Risda; Viola, Grisel; Maryam, Siti; Syahlan, Fatra; Nugraha, Derry (PT Agung Media Publisher, 2025)
This study explores how reading corners can increase students’ interest in reading and improve literacy skills at SD Negeri Cilondong, located in Cihanyawar Village, Sukabumi Regency. The reading corners were created as a solution to the lack of reading materials and poor reading environments often found in rural schools. Using the Participatory Action Research (PAR) approach, the study involved 80 students from grades 1 to 6, along with teachers and school staff, in a process of planning, implementing, and evaluating the reading corner activities. Data were collected through questionnaires, reading logs, and group discussions. The reading corners were filled with storybooks, comics, science books, picture books, and folk tales. After several months, the results showed clear improvements: 68.8% of students enjoyed reading more, 75.1% actively used the reading corners, and over 70% showed better reading comprehension, vocabulary, and fluency. Most students visited the corners regularly and many borrowed books to read at home. This study shows that a simple, low-cost reading corner, developed with community involvement, can significantly help improve reading habits and literacy in rural elementary schools.